Клініко-діагностичні особливості та лікування синдрому біологічно неактивного гормону росту - Спринчук, Н. А.; Самсон, О. Я. (Clinical Endocrinology and Endocrine Surgery, 2010)
Molecular genetic features of syndrome of biologically inactive growth hormone was shown. Phenotype of patients with the syndrome of biologically inactive growth hormone was described. Clinico-laboratory and differential diagnosis of this pathology were depicted. Use of samples on sensitivity to growth hormone in patients with the above pathology to confirm the diagnosis and adequate for the purpose therapy of growth hormone was proved. The comparative analysis of somatotropin in the treatment of group of children with the syndrome of biologically inactive growth hormone deficiency and classical deficiency of growth hormone was made.